Optimizing Merremia aegyptia and Calotropis procera biomass application rates in kale cultivation under semi-arid conditions (Acta Scientiarum. Agronomy, 2024)
This study aimed to optimize both agronomically and economically leaf green mass productivity of kale and its agronomic components when fertilized with equivalent biomass amounts of the hairy woodrose (Merremia aegyptia L.) and roostertree (Calotropis procera Ait.) spontaneous species from the Caatinga biome in two cropping seasons. The experimental design was in randomized blocks with five treatments and five replications. The treatments consisted of equivalent biomass amounts of hairy woodrose and roostertree at doses of 16, 29, 42, 55, and 68 ton ha-1, on a dry basis. In each experiment, a treatment without fertilization (control) and a treatment with chemical fertilization were used. The maximum optimized physical efficiencies of the kale commercial leaf productivity and number of leaf packets per square meter were 16.92 ton ha-1 and 6.97, respectively, when the amounts of the green manure biomass of 56.41 and 48.63 ton ha-1 were incorporated into the soil. The optimized maximum net income of 47,841.44 BRL ha-1 and rate of return of 2.47 reals for each real invested were obtained when the amounts of the green manure biomass were 53.26 and 64.31 ton ha-1 added to the soil. The use of M. aegyptia and C. procera biomass as green manure is a viable technology for kale producers in monocropping in a semi-arid environment.